Influencing factors of leakage in patients with urostomy and research progress of nursing interventions (尿路造口患者渗漏的影响因素及护理研究进展) - WANG Ping (王萍); WANG Jun (王俊); JI Xuebi (吉学碧); WANG Haifeng (王海峰) (中西医结合护理, 2025)
Leakage is a common complication in patients with urostomy after bladder cancer surgery, affecting patients' quality of life and psychological health. Recently, leakage in patients with urostomy has received widespread attention both at home and abroad. Effectively addressing the leakage can not only reduce the incidence of peristoma skin complications, but also improve the quality of life of patients with urostomy, which is of great clinical significance. This paper systematically reviewed the influence of leakage, related factors and nursing measures for patients undergoing urostomy, aiming to provide a reference basis for the future development of clinical care program and prognosis of leakage in urostomy patients with bladder cancer. (尿路造口渗漏是膀胱癌术后常见并发症, 影响患者生活质量及心理健康。目前, 造口底盘的渗漏问题在国内外都受到了广泛的关注。有效解决这一问题不仅能显著减少造口周围皮肤并发症的临床发生率, 还能明显提升尿路造口患者的生活质量, 具有重要的临床意义。本研究通过系统综述尿路造口患者渗漏的影响、相关因素及护理措施, 旨在为今后制订膀胱癌尿路造口患者渗漏的临床护理方案及预后康复提供参考依据。)